INTERNATIONAL LEGAL REGIME ON GENE PATENTING IN PLANTS (NATIONAL CAPITAL LAW JOURNAL, 2019)
NA
Keywords: Gene Patenting; International Legal Regime; Plants; TRIPS Agreement; Biotechnology; Intellectual Property Rights; Convention On Biological Diversity; Nagoya Protocol; Access And Benefit Sharing; Sovereign Rights